Energy Finance and Carbon Finance: Key Roles of the Financial Community in Addressing Climate Change - Li, Wenyang (International Journal of Social Sciences and Public Administration, 2024)
Climate change presents a formidable challenge to humanity, demanding urgent action from all sectors of society. The financial community, with its significant influence and resources, plays a crucial role in addressing this global crisis. This paper explores the roles of energy finance and carbon finance within the financial sector in the context of mitigating climate change. It examines the mechanisms through which financial institutions can contribute to the transition towards low-carbon economies, including investment strategies, risk management approaches, and the development of innovative financial instruments. Furthermore, it discusses the potential synergies between energy finance and carbon finance in facilitating the transition to a sustainable energy system and reducing greenhouse gas emissions. By leveraging their expertise and resources, financial institutions can become key enablers of climate action, fostering the necessary investments and incentives for the decarbonization of the global economy.